Evaluation of hospital layout for optimal entity flow using movement cost - Soron?o, Kristian A.; Juanga, Jean Marie V. (2019)
Hospitals play an important role in maintaining the overall state of public health. While there are many guidelines towards keeping the sanitation of the building and its facilities, there are few guidelines about planning the layout of the hospital ? particularly in relation towards the movement its users. To solve this, the study aimed to determine an optimal proximity layout based on the flow of these entities. To do this, the study conducted a survey to determine the baseline travel cost of the different entities in the hospital as well as the travel frequency and trip difficulty rating between the spaces in the building. The data gathered was then analyzed using a variant of the movement cost formula used by Padgaonkar (2004). The results of the study not only coincides with existing guidelines but also added to it by being more specific. One notable result was from the diagnostic facilities, wherein it was identified that X-Ray Facilities and the Laboratory Department had the highest value of movement cost in relation towards to the Emergency Room and the In-patient Wards. As such, it is advised that the X-Ray Rooms and the entry of the Laboratory Department be in closer proximity to the access to these spaces in comparison to the other spaces in the Diagnostic Facilities. Another suggestion derived from the results is that In-Patient Wards be composed of rooms that accommodate different number of patients with more private rooms being farther from nurse stations.
Thesis (BS Architecture)--University of the Philippines Mindanao,2019